METHODOLOGY FOR ENHANCING STUDENTS’ ORAL ACTIVITY THROUGH A SYSTEM OF HEURISTIC TASKS (Universal International Scientific Journal, 2026)
This article is dedicated to the scientific and practical exploration of theeffectiveness of a heuristic task system in enhancing students’ oral activity. The study analyzes theintegration of heuristic methods into the pedagogical process and their role in developing students’independent thinking and communication skills. The article presents the principles of designing heuristictasks, methods for their application in classroom practice, and criteria for assessing oral activity from ascholarly perspective. The findings demonstrate that heuristic approaches significantly contribute to thedevelopment of critical thinking, creative communication, and verbal skills among students, therebyimproving the overall quality of educational interaction
Keywords: heuristic tasks; oral activity; students